The effect of balance and kinetic coordination trainings on the improvement of the accuracy of shooting with the weak foot for football buds. - medjrali ahmed; chenati ahmed (sports creativity, 2025)
The effect of balance training placement and motor training on the skillful penformance of foot ball buds . -the aim of the study is to find out the effect training…… -by zasing on scent fic theoies , the ses encher is ed the experimental method to design the tivo greups by meams of tribal and postmeas urment to suit the format of the researh objectives . The exerimental faitor was appliecl to reseanch sample onsisting of 30 and i twas diuided into two experime,tal and external groups using the experimontal methoch. Results : 1- theve are differencesc wirth sttiscal sigm ficance in the effect of balaunce and coordinati on exereise on the skill performamce of the skill perfomance of the weak foot betweeu the experimental and control groups in the semote testes in favor of the experimental group. 2-it is necenany to tnclude training program , especially inthe training stagest balanche and coordinatin of the movement on the left and night side of this stage which characterized bay fetithty and dynamic in deplen dence to enrich the balance of maltipke motor behaviors to retuar positvely to the skill perfomance of weak foot .